Indicators to assess the quality of organizational attention: first steps towards a measurement instrument - Bigolin, Fernanda (2018)
Organizations increasingly have access to varied and sophisticated information about their internal and external environments. While there is the general belief that accessing high quality and sophisticated information leads to more effective decisions, this is not necessarily true. In a number of disciplinary fields, from economics to psychology and technology, scholars are emphasizing that information overload produces confusion and reduces consistent decision-making. This paper focuses organizational attention and presents a tool to assess the quality of organizational attention mediated by technology. This instrument was tested and will soon be applied in a pilot study to further refine it.